The Effectiveness Of Rinsing With 10% Forest Honey Solution on Plaque Accumulation in Fixed Orthodontic Patients - Husna, Salsabila Aliyah; Dinar, Nushita; Lestari Vidyahayati, Indah (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Fixed orthodontic appliances to correct malocclusion and maintain periodontal tissues have complex designs and appliance shapes that can accelerate plaque formation. Preventive efforts to maintain oral hygiene status during treatment of fixed orthodontic devices can be done by using alternative mouthwashes made from natural ingredients, one of them is forest honey. This study aimed to determine the effectiveness of rinsing with 10% forest honey solution on reducing plaque accumulation in fixed orthodontic appliance patients. Type of research was Quasi Experiment with Pre-Post Test with Control Group Design. A sample of 40 people was divided into a control group rinsing with distilled water and a treatment group rinsing with 10% forest honey solution for 4, 6, and 8 days. Assessment of plaque accumulation using the Orthodontic Plaque Index (OPI). Data test results were normally distributed and homogen (p>0.05). One Way Anova test showed a significant difference between OPI before and after in the control group and treatment group (p<0,05). Post Hoc LSD results showed insignificant values ​​(p>0.05) in group K (aquadest) and group P1 (4 days), while in group P2 (6 days) and P3 (8 days) rinsing 10% forest honey solution showed significant values ​​(p<0.05). Rinsing with 10% forest honey solution for 6 days and 8 days is effective in reducing plaque accumulation in fixed orthodontic appliance patients.